Do FDA label changes work? Assessment of the 2010 class label change for proton pump inhibitors using the Sentinel System's analytic tools. Issue 3 (2nd February 2018) - Sobel, Rachel E.; Bate, Andrew; Marshall, James; Haynes, Kevin; Selvam, Nandini; Nair, Vinit; Daniel, Gregory; Brown, Jeffrey S.; Reynolds, Robert F.
Abstract: Purpose: To pilot use of the US Food and Drug Administration's (FDA's) Sentinel System data and analytic tools by a non‐FDA stakeholder through the Innovation in Medical Evidence Development and Surveillance system of the Reagan Udall Foundation. We evaluated the US FDA 2010 proton pump inhibitor (PPI) class label change that warned of increased risk of bone fracture, to use PPIs for the lowest dose and shortest duration, and to manage bone status for those at risk for osteoporosis. Methods: The cohort consisted of adults aged 18 years or older prescribed PPIs without fracture risk factors. We evaluated incident and prevalent uses of the 8 PPIs noted in the label change. Outcomes evaluated before and after label change were PPI dispensing patterns, incident fractures, and osteoporosis screening or interventions. Consistent with FDA use of descriptive tools, we did not include direct comparisons or statistical testing. Results: There were 1 488 869 and 2 224 420 incident PPI users in the before [PRE] and after [POST] periods, respectively. Users with 1 year or more of exposure decreased (8.4% vs 7.5%), as did mean days supplied/user (130.4 to 113.7 d among all users and 830.8 to 645.4 d among users with 1 y or more of exposure). Osteoporosis screening and interventions did not appear to increase, but the proportion of patients with fractures decreased (4.4% vs 3.1%). Prevalent user results were similar. Conclusions: This analysis demonstrated the ability to use Sentinel tools to assess the effectiveness of a label change and accompanying communication at the population level and suggests an influence on subsequent dispensing behavior.